INTERACTIVE LEARNING MEDIA BASED ON THE LECTORA INSPIRE APPLICATION IN THEMATIC LEARNING IN GRADE IV ELEMENTARY SCHOOL - Hasnanto, Anton Tri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to develop interactive learning media based on the Lectora Inspire application in thematic learning of grade IV Elementary School. The background of the problem shows that the use of innovative media in learning is still low. The solution is to develop Lectora Inspire learning media that can improve student motivation and learning outcomes. The research method used is research and development (R&D) with the ADDIE model. The subjects of the study were 45 grade IV students, of which 15 students were in small-scale trials and 30 students were in large-scale trials. Data collection techniques were carried out by observation, interviews, questionnaires and documentation. Data analysis used quantitative descriptive analysis techniques. The instruments used were assessment scales to determine the feasibility of language, media, and materials as well as the response to the attractiveness of the product to students with a Likert scale arranged in the form of a checklist. The results of expert validation showed that this media was very valid with a percentage above 80%. Trials in two schools showed a positive response from students, with a very interesting percentage reaching 98.4% and 96.5%. The conclusion of this study is that the Lectora Inspire media is effective in supporting thematic learning and increasing student involvement.